An investigation of coastal vulnerability and internal consistency of local perceptions under climate change risk in the southwest part of Bangladesh. (1st February 2019) - Rakib, M.A.; Sasaki, Jun; Pal, Sosimohan; Newaz, Md. Asif; Bodrud-Doza, Md.; Bhuiyan, Mohammad A.H.
Abstract: Climatic threats force disruption on community lifestyles by impairing social factors, the fundamental components of ensuring social sustainability. This study investigates the situational factors affecting the consequences on coastal livelihoods, and social activities; it also considers the effectiveness of traditional knowledge in reducing possible risks. Both qualitative and quantitative methods were employed, including questionnaire survey for identifying the local perception of climatic impacts alongside the impacts on daily activities. Interviews, field observations, and multivariate analyses were performed to explain the vulnerability status in coastal communities. Results show that most livelihood sectors were severely affected by the long-term and repeated actions of climatic hazards, such as cyclones, associated with a number of unavoidable risks making people susceptible to damages in social wellbeing. In addition, saltwater intrusion damages drinking water supply and crop farming, which can cause diseases among coastal communities, but very few attempts have been made to provide alternative sources of drinking water at a household level. Moreover, principal component analysis (PCA) and cluster analysis (CA) revealed significant interfaces between local perceptions and the socio-and agro-environmental factors changing the overall status of regional hazards. Thus, the situation exhibits coastal hazards, social vulnerability, and social crisis. Local people use their traditional knowledge to cope with various levels of crisis under vulnerable conditions, but sometimes doing so exceeds their capacity owing to the unwanted changes in climatic variables and knowledge gaps or uncertainties. Challenges on the basis of the problematic points should be noted, however, it would be more significant to achieve social sustainability under adverse climatic conditions. Highlights: Climatic impacts triggering salinity problems in the coastal area of Bangladesh. Coastal livelihood affected by coastal hazards and associated salinity problems. Potable water crisis threatening coastal lifestyle. Traditional local knowledge becoming useless for predicting coastal hazards due to consequences of climate change. PCA and CA tools used to validate the consistency in local perceptions.